(untitled) (Bangladesh Journal of Anatomy, 2014)
Context: Estimation of facial height and nasal length from digital photography is important to evaluate and planning surgical treatment of facial trauma, facial defect and post traumatic deformity. So facial height and nasal length values are of great use in plastic surgery and reconstructive surgery. These values are also important for identification of a person in forensic anthropology and archeology. The reliability of estimation of facial height from nasal length by using multiplication factor is high. The values of facial height and nasal length vary among populations. Materials and Method: This is a cross sectional, analytical type of study conducted in the Department of Anatomy, Sir Salimullah Medical College, Dhaka from January 2010 to June 2011. One hundred (100) Bangladeshi 25 to 45 years old women were selected for the study. Fourth class female employees of Sir Salimullah Medical College and Mitford Hospital and part time housemaids of Mitford area were selected by purposive sampling as study subjects. Results: The values of facial height and nasal length were 17.949 ± 1.3111cm and 5.179 ± 0.5349cm respectively. Multiplication factor for measuring facial height from nasal length was 3.49 ± 0.2864 (Mean ± SD). No significant difference was found between the measured and estimated facial height from nasal length. Conclusion: The anthropometric base line data of different facial dimensions might help the surgeons in diagnosing and treating reconstructive cases DOI: http://dx.doi.org/10.3329/bja.v11i2.20669 Bangladesh Journal of Anatomy, July 2013, Vol. 11 No. 2 pp 50-53